Awareness of parents of hearing-impaired children about the importance of speech-language therapeutic interventions (Journal of Fatima Jinnah Medical University, 2021)
Background: The importance of parental involvement of hearing-impaired children in their child's speech therapy cannot be denied.  The current study aimed to determine parental awareness and involvement in the Speech-language therapeutic interventions of hearing-impaired children.Subjects and methods: This was a cross-sectional study design, and a purposive sampling technique was used. Data were collected from 45 parents (male=32, female=13) of hearing-impaired children whose children received speech therapy from special education centers and schools of Gujranwala. The duration of the study was nine months, from June 2019 to February 2020. A related questionnaire was developed with the literature, and expert opinions (Cronbach's α=0.894) were used to assess parental awareness and involvement in speech therapeutic interventions. Data entered and analyzed by SPSS version 23. Descriptive statistics were used to describe demographic variables (age, gender) of the participants. Frequency and percentage were used to access the awareness and involvement of the parents of hearing-impaired children.Results: Parental awareness survey showed that a total of 15 (33.3%) parents, both mother, and father, strongly agreed, and 24 (53.3%) agreed that speech therapy would be beneficial for their child. And results related to parents' involvement showed that 21 (46.7%) parents, both mother, and father, agreed, and 15 (33.3%) strongly agreed on their child's active involvement in speech therapy plans.Conclusions: The study concluded that most parents understand the importance of parental awareness and involvement in the therapeutic intervention of hearing-impaired children.
Keywords: Hearing impairment; Parental awareness; Parental involvement; Therapeutic interventions